2002
DOI: 10.1038/416438a
|View full text |Cite
|
Sign up to set email alerts
|

Rac function and regulation during Drosophila development

Abstract: Rac GTPases regulate the actin cytoskeleton to control changes in cell shape. To date, the analysis of Rac function during development has relied heavily on the use of dominant mutant isoforms. Here, we use loss-of-function mutations to show that the three Drosophila Rac genes, Rac1, Rac2 and Mtl, have overlapping functions in the control of epithelial morphogenesis, myoblast fusion, and axon growth and guidance. They are not required for the establishment of planar cell polarity, as had been suggested on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
334
2
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(354 citation statements)
references
References 29 publications
11
334
2
7
Order By: Relevance
“…In contrast, however, no defects in planar polarity establishment were observed in clones of cells in the eye and the wing that were triply mutant for null alleles of DRac1, DRac2, and Mtl. These data indicate that DRac proteins are not essential in the generation of planar polarity and that the effects seen with the dominant negative Rac mutant proteins may be attributable to cross-inhibition or cross-activation of other pathways (Hakeda- Suzuki et al 2002). The latter studies do not, however, exclude a possible involvement of the DRac proteins in signaling pathways that are activated by Fz.…”
Section: Planar Polaritymentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast, however, no defects in planar polarity establishment were observed in clones of cells in the eye and the wing that were triply mutant for null alleles of DRac1, DRac2, and Mtl. These data indicate that DRac proteins are not essential in the generation of planar polarity and that the effects seen with the dominant negative Rac mutant proteins may be attributable to cross-inhibition or cross-activation of other pathways (Hakeda- Suzuki et al 2002). The latter studies do not, however, exclude a possible involvement of the DRac proteins in signaling pathways that are activated by Fz.…”
Section: Planar Polaritymentioning
confidence: 84%
“…One potential caveat is that the above-described Rac1 studies relied mainly on the use of dominant negative and constitutively active mutant forms of Rac. In more recent studies, an extensive phenotypic analysis of loss-of-function mutations in each of the endogenous Rac genes (including DRac1, DRac2, and Mtl) was performed (Hakeda- Suzuki et al 2002;Ng et al 2002). Consistent with the dominant negative and activated DRac mutant analyses, these studies showed that the DRac genes have overlapping functions in the control of dorsal closure, myoblast fusion, and axon growth and guidance.…”
Section: Planar Polaritymentioning
confidence: 92%
“…Cdc42 seems not to play a major role in myoblast fusion (Schä fer et al, 2007) in contrast to Rac (see below). The first actin regulators that were identified to be important for myoblast fusion were the small rac-GTPases rac1, rac2 (Luo et al, 1994;Doberstein et al, 1997;Hakeda-Suzuki et al, 2002), and kette, the Drosophila homologue of Nap1/Hem-2 (Schröter et al, 2004). Interestingly, kette interacts genetically with the fcm-specifically expressed gene blow (Schröter et al, 2004).…”
Section: Regulation Of Actin Polymerization During Myoblast Fusionmentioning
confidence: 99%
“…We first examined the function of Rac1 in dendritic growth and branching of DA neurons in Drosophila embryos. We used Rac1 J11 , a null allele previously characterized based on biochemical and genetic criteria Hakeda-Suzuki et al, 2002). We used Gal4 109(2)80 (Gao et al, 1999) to drive the expression of GFP in DA neurons in Rac1 J11 mutant embryos and did not observe gross defects in dendritic branching patterns in later embryogenesis stages (data not shown).…”
Section: Rac1 Is Required For the Development Of Higher-order Dendritmentioning
confidence: 99%